2023
DOI: 10.1007/s13577-023-00882-x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the characteristics of primary radioresistant cervical cancer using single-cell transcriptomics

Abstract: Radioresistance is a major cause of radiotherapy failure among patients with cervical cancer (CC), the fourth most common cause of cancer mortality in women worldwide. Traditional CC cell lines lose intra-tumoral heterogeneity, posing a challenge for radioresistance research. Meanwhile, conditional reprogramming (CR) maintains intra-tumoral heterogeneity and complexity, as well as the genomic and clinical characteristics of original cells and tissues. Three radioresistant and two radiosensitive primary CC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Recently, CR technology was used to establish three radioresistant and two radiosensitive cell lines from cervical cancer patients’ specimens and verified their molecular characteristics and biological changes including growth kinetics, immunofluorescence, clone forming assay xenografting, and immunohistochemistry vitro and in vivo [ 58 ]. The results of single-cell RNA (sc-RNA) sequencing analysis showed that 38.1% of cells in radiosensitive CR cell lines aggregated in the G2/M cell cycle phase which is sensitive to radiation compared to 20.83% of cells in radioresistant CR cell lines.…”
Section: Conditional Cell Reprogramming (Ccr) At Ali For Modeling Hos...mentioning
confidence: 99%
“…Recently, CR technology was used to establish three radioresistant and two radiosensitive cell lines from cervical cancer patients’ specimens and verified their molecular characteristics and biological changes including growth kinetics, immunofluorescence, clone forming assay xenografting, and immunohistochemistry vitro and in vivo [ 58 ]. The results of single-cell RNA (sc-RNA) sequencing analysis showed that 38.1% of cells in radiosensitive CR cell lines aggregated in the G2/M cell cycle phase which is sensitive to radiation compared to 20.83% of cells in radioresistant CR cell lines.…”
Section: Conditional Cell Reprogramming (Ccr) At Ali For Modeling Hos...mentioning
confidence: 99%